Carbon Dioxide Activation by a Palladium Terminal Imido Complex - Goodner, Stephen J.; Grünwald, Annette; Heinemann, Frank Wilhelm; Munz, Dominik (Australian Journal of Chemistry, 2019)
We recently reported the first example of a palladium(ii) terminal imido complex. We proposed that this complex features exceptional high nucleophilicity at the nitrogen atom and a peculiar zwitterionic electronic structure with an anti-bonding highest-occupied molecular orbital (HOMO). This complex swiftly activated moderately acidic CH, OH, and NH bonds and also reacted with dihydrogen. However, unambiguous nucleophilic reactivity with substrates not featuring a hydrogen atom could not be observed. Herein, we now show that this nucleophilic complex also reacts with CO2 to give a ring-strained four-membered palladium(ii) carbamate complex. Remarkably, the same product is obtained in the reaction of the related bisamido complex, albeit at a slower reaction rate. Density functional theory calculations indicate that the addition of CO2 does not proceed via initial 1,2-addition across the Pd-N bond, but instead through nucleophilic attack by the imido (amido respectively) nitrogen atom.
CRIS-Team Scopus Importer:2019-09-24